Growth and Yield of Granolla Bulbs on Organic Mulch and POC Formulation - Adnan Adnan (International Journal Labs, 2022)
The research was conducted from June to December 2019, Rejang Lebong Regency. on a plateau 600 m above sea level. Factorial Randomized Block Design (RBD) study. The first treatment was organic mulch (M), M1 = without mulch, M2 = banana leaves, M3 = rice husks, M4 = coffee husks. The POC (O) treatment is O0 = Without POC, O1 = POC 50 ml/liter of water, O2 = POC 75 ml/liter of water and O3 = POC 100 ml/liter of water. The number of plants is 288 potato seed tubers. The results of the variance of the single treatment of liquid fertilizer and single treatment of mulch had a very significant effect on: the number of main stems and shoots, fresh weight, stem diameter, but had no significant effect; plant height, number of tubers and dry weight. The combination of treatments had a very significant effect: number of main stems, plant height, number of shoots, fresh weight and tuber diameter. Liquid fertilizer and mulch have interactions: plant height, number of main stems, number of shoots, wet weight and tuber diameter.